2023
DOI: 10.1021/acschembio.2c00685
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Tambjamine Gene Cluster in Streptomyces Suggests Convergent Evolution in Bipyrrole Natural Product Biosynthesis

Abstract: While bacterial natural products are a valuable source of therapeutics, the molecules produced by most biosynthetic gene clusters remain unknown. Tambjamine YP1, produced by Pseudoalteromonas tunicata, is partially derived from fatty acids siphoned from primary metabolism. A structurally similar tambjamine produced by Streptomyces, BE-18591, had not been linked to a gene cluster. Using enzymes putatively implicated in the construction of these two tambjamines, we used sequence similarity networks and gene knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This is probably best studied within the antimicrobial NPs with new examples being increasingly discovered. Convergent evolution can be via evolutionary convergence of pathways to deliver the same molecule (Fischbach, 2009;Grenade et al, 2021; e.g beta-lactams (Liras and Martín, 2006), fosfomycin in Pseudomonas and Streptomyces (Kim et al, 2012), gerumycin and dentigerumycin (Sit et al, 2015), tambjamines in Pseudoalteromonas and Streptomyces (Grenade et al, 2023) or to deliver highly similar molecules that have converged on the same cellular targets (Fischbach, 2009) (e.g. five structural classes of antibiotic targeting the bacterial ribosome (Hansen et al, 2003), Lipid II (Breukink and Kruijff, 2006), and bacterial cell wall synthesis (Sarkar et al, 2017)).…”
Section: ) What Types Of Mutations Are Required To Deliver Innovation...mentioning
confidence: 99%
“…This is probably best studied within the antimicrobial NPs with new examples being increasingly discovered. Convergent evolution can be via evolutionary convergence of pathways to deliver the same molecule (Fischbach, 2009;Grenade et al, 2021; e.g beta-lactams (Liras and Martín, 2006), fosfomycin in Pseudomonas and Streptomyces (Kim et al, 2012), gerumycin and dentigerumycin (Sit et al, 2015), tambjamines in Pseudoalteromonas and Streptomyces (Grenade et al, 2023) or to deliver highly similar molecules that have converged on the same cellular targets (Fischbach, 2009) (e.g. five structural classes of antibiotic targeting the bacterial ribosome (Hansen et al, 2003), Lipid II (Breukink and Kruijff, 2006), and bacterial cell wall synthesis (Sarkar et al, 2017)).…”
Section: ) What Types Of Mutations Are Required To Deliver Innovation...mentioning
confidence: 99%
“…1, bottom). [38][39][40][41][42] Despite the structural diversity of prodiginine-related natural products, their biosynthesis resorts to clustered genes, encoding for non-ribosomal peptide synthetases (NRPS) of type II. 36,43 Using the synthesis of prodigiosin (1) as representative example, the assembly employs a convergent route with two key precursors, namely the bipyrrole part (4-methoxy-2,2′-bipyrrole-5-carbaldehyde, MBC 3a) and the monopyrrole part (2-methyl-3-amylpyrrole, MAP 4a), which are consolidated in an ATP-catalysed condensation reaction to give the conjugated tripyrrole scaffold of prodigiosin (1) (Fig.…”
Section: Biosynthesis and Condensing Enzymesmentioning
confidence: 99%
“…The diversity of this nitrogen-substituent led to a large variety of derivatives and biological applications. From 2010, Tambjamine derivatives were reported with potent antimicrobial, anticancer, and antimalarial bioactivities [104][105][106][107][108][109][110][111][112]. In 2010, Banwell, Pessoa et al reported the first anti-Malassezia potential of some synthetically derived tambjamines [113].…”
Section: Apoptosis Inducersmentioning
confidence: 99%